2023
DOI: 10.1080/2162402x.2023.2174721
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Ablative Radiation Therapy in 3 Fractions Induces a Favorable Systemic Immune Cell Profiling in Prostate Cancer Patients

Abstract: The impact of radiotherapy (RT) on immune cell status in prostate cancer (PCa) is only partially determined. The aim of this study was to assess the effect of different RT strategies on peripheral B, T, and Natural killer (NK) lymphocytes at precise longitudinal time-points in PCa. 18 patients treated with stereotactic body radiation therapy (SBRT) (40 Gy/3FRX), definitive moderate-hypofractionation (62 Gy/20FRX), or post-operative conventional-fractionation RT (66–69 Gy/30FRX) were prospectively evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Consistent with this concept, a study on early-stage NSCLC patients demonstrated that the proliferation of circulating CD8 + T cells was increased by SBRT with a daily dose of 10 Gy or less but not with higher doses [37]. Nonetheless, an analysis of prostate cancer patients and metastatic breast cancer patients did not observe any difference among varying daily doses [44,72], suggesting that the relationship between CD8 + T cell responses and the daily dose should be investigated in detail.…”
Section: Factors That Influence Rt-induced Cd8 + T Cell-responsesmentioning
confidence: 90%
See 1 more Smart Citation
“…Consistent with this concept, a study on early-stage NSCLC patients demonstrated that the proliferation of circulating CD8 + T cells was increased by SBRT with a daily dose of 10 Gy or less but not with higher doses [37]. Nonetheless, an analysis of prostate cancer patients and metastatic breast cancer patients did not observe any difference among varying daily doses [44,72], suggesting that the relationship between CD8 + T cell responses and the daily dose should be investigated in detail.…”
Section: Factors That Influence Rt-induced Cd8 + T Cell-responsesmentioning
confidence: 90%
“…Similarly, another study showed that circulating CD8 + T cells reactive to tumor-associated antigens were increased in two prostate cancer patients at 1 month after RT [43]. Palermo et al compared the effects of varying RT schemes, including SBRT, hypofractionated RT, and conventionally fractionated RT, and revealed that the proportion of CD8 + T cells among circulating T cells was increased after RT regardless of the RT scheme [44]. Notably, effector memory CD8 + T cells and VISTA-expressing CD8 + T cells were increased only in patients undergoing SBRT.…”
Section: Changes In Cd8 + T Cells Following Rtmentioning
confidence: 99%
“…The results showed that conventional radiotherapy has a negative impact on systemic immunity, resulting in an increase in neutrophils/lymphocytes and a decrease in total lymphocyte count. In contrast, SBRT increased B cell, central memory T cell, and effector CD8 + T cell infiltration in the TME, as well as increased CD8/Treg ratio (29). In summary, SBRT could activate the immune system through multiple pathways and create an ideal TME for subsequent immunotherapy (Figure 1).…”
Section: The Interplay Between Sbrt and Antitumour Immune Responsementioning
confidence: 99%
“…For example, the analysis of paired lung cancer samples following SBRT revealed an increase in the diversity of the T cell receptor repertoire and programmed cell death ligand 1 (PD-L1) expression, while no significant increase of CD8 + T cell and IFN expression was observed within tumour tissues (33). In addition to PD-L1, SBRT can also significantly up-regulate V-domain immunoglobulin suppressor of T cell activation (VISTA) expression in CD8 + T cells (29). It is worth noting that not all immune checkpoints are elevated following SBRT.…”
Section: The Interplay Between Sbrt and Antitumour Immune Responsementioning
confidence: 99%
“…Immune monitoring of the 18 patients showed that RT can affect the balance of systemic immune cells, with the main differences observed between SBRT and conventionally fractionated RT [106]. While conventional RT had a long-term negative effect on the sys-temic immune profile, SBRT favorably impacts immune response in terms of increased B cells, central-memory and effector-memory CD8 + T cells, along with decreased Treg cells after treatment.…”
Section: Complicationsmentioning
confidence: 99%